The Impact of Rural-Urban Migration on the Health of the Left-behind Parents - Xiang Ao; Dawei Jiang; Zhong Zhao (Institute for the Study of Labor (IZA), 2015)
Since the reform and opening up in 1978, China has begun a period of rapid industrialization and urbanization. Along with an increasing number of rural people migrating to urban area for jobs, there are a considerable number of elderly parents left behind in the rural area. The impact of migration of the adult children on the health of their left-behind parents is ambiguous. On the one hand, the additional income from the children's jobs can allow their parents to afford better health care and nutrition; on the other hand, the migration necessarily reduces the amount of time the children have to take care of their parents. This paper uses the Rural Urban Migration in China data to empirically investigate the effect of adult children's migration on the health of the left-behind parents. Based on a linear probability model with instrumental variable correction, we find that having one additional adult child migrated to an urban area increases the probability of the left-behind elderly parents being in poor health condition by about 8%. Furthermore, parents having only one child, from low-income households, or aged above 60 years are affected more. Our results point out that the parents with only one child is the most vulnerable group and highlight the importance of establishing a formal care system for the rural elderly to complement the traditional family care in rural China.
Keywords: O15; J14; I15; 330; rural-urban migration; health; left-behind parents; China